2016
DOI: 10.1016/j.exer.2016.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Connexin23 deletion does not affect lens transparency

Abstract: While connexin46 (Cx46) and connexin50 (Cx50) are crucial for maintaining lens transparency and growth, the contributions of a more recently identified lens fiber connexin, Cx23, are poorly understood. Therefore, we studied the consequences of absence of Cx23 in mouse lenses. Cx23-null mice were generated by homologous Cre recombination. Cx23 mRNA was abundantly expressed in wild type lenses, but not in Cx23-null lenses. The transparency and refractive properties of Cx23-null lenses were similar to wild type l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…Transcripts for a fourth lens connexin, Cx23, have been identified in zebrafish embryo and mouse lenses [ 10 12 ]. In mouse lens fiber cells, the abundance of Cx23 protein is similar to Cx46, but lower than Cx50 [ 13 ]; however, Cx23 knockout mice have transparent lenses [ 14 ]. In the human lens, expression of Cx23 has not been reported, and it has been suggested that the Cx23 gene is inactivated in primates [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Transcripts for a fourth lens connexin, Cx23, have been identified in zebrafish embryo and mouse lenses [ 10 12 ]. In mouse lens fiber cells, the abundance of Cx23 protein is similar to Cx46, but lower than Cx50 [ 13 ]; however, Cx23 knockout mice have transparent lenses [ 14 ]. In the human lens, expression of Cx23 has not been reported, and it has been suggested that the Cx23 gene is inactivated in primates [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, these findings place Cx31.1 into an unusual category of having little or no ability of being able to form functional gap junction channels when expressed in the absence of other connexins. Although Cx23 is another connexin that fails to form gap junction channels, Cx23 transcripts have not been discovered in primate cDNA libraries suggesting the GJIC incompetency of Cx23 is likely due to gene inactivation, unlike Cx31.1, which has been identified at the protein and transcript level in several human cell types ( Sonntag et al, 2009 ; Berthoud et al, 2016 ). Thus, Cx31.1 is in a unique category of connexin isoforms exhibiting little capacity to form gap junction channels on its own in tissue-relevant keratinocytes, even though it is present at the mRNA and protein levels in keratinocytes and other cell types ( Goliger and Paul, 1994 ; Di et al, 2001 ; Kibschull et al, 2004 ; Shurman et al, 2005 ; Wiszniewski et al, 2007 ; Dere et al, 2008 ; Wang et al, 2009 ; Serre-Beinier et al, 2009 ; Zhang et al, 2012 ; Kibschull et al, 2014 ; Zhai et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cx46 forms gap junction channels between fiber cells in bovine ( Paul et al, 1991 ; Tenbroek et al, 1992 ), chicken ( Biswas et al, 2010 ), mouse ( Gong et al, 1998 ; Berthoud et al, 2016 ), and monkey ( Lo et al, 1996 ) lenses. The current evidence based on the association of cataract development with Cx46 mutations strongly supports the notion that Cx46 also forms gap junction channels in human fiber cells ( Jiang, 2010 ; Retamal et al, 2015 ; Berthoud and Ngezahayo, 2017 ; Berthoud et al, 2020 ).…”
Section: Connexins In the Lensmentioning
confidence: 99%